Metagenomic insights into differences in environmental resistome profiles between integrated and monoculture aquaculture farms in China. (November 2020) - Xu, Chunyan; Lv, Ziquan; Shen, Yingbo; Liu, Dejun; Fu, Yulin; Zhou, Lan; Liu, Weiwen; Chen, Kun; Ye, Hailing; Xia, Xi; Xia, Junjie; Wang, Yang; et al.
Highlights: Integrated farms had a greater number/abundance of ARG and MGE subtypes. Integrated farms had higher abundance of colistin/tigecycline resistance genes. Relationships among ARGs, MGEs, and microbial taxa were more complex in integrated farms. Abstract: Cumulative research on resistomes and microbiomes from aquatic environments has revealed that both integrated freshwater and monoculture freshwater aquaculture systems can cause the development and dissemination of antibiotic resistance genes (ARGs) and associated mobile genetic elements (MGEs). However, few studies have examined differences in resistomes between the different aquaculture modes, and those that do have focused on antibiotic residues or individual resistance genes. In the current study, we collected 44 environmental samples from two monoculture freshwater aquaculture farms and four integrated farms (two duck and fish farms, two laying duck and fish farms) in Guangdong, China, in 2018. After measuring the concentrations of antibiotic residues in the samples, we characterized MGEs and ARGs and examined their association with potential bacterial hosts in the microbial communities using high-throughput sequencing-based metagenomic and network analyses. We then compared the resistome profiles of the different aquaculture models. We found that the number and total relative abundance of ARG and MGE subtypes in the integrated (fish and duck/laying duck) farm samples were significantly higher than those in samples from monoculture freshwater aquaculture farms. Specifically, both the mobile colistin resistance genes mcr variants and tigecycline resistance gene tet (X) variants in integrated farms exhibited higher total relative abundance than that in monoculture farms. Moreover, the interrelationships among ARGs and microbial taxa, ARGs and MGEs, and MGEs and microbial taxa in the integrated farm samples were also more complex than those observed in monoculture freshwater aquaculture farm samples. Meanwhile, the species of Acinetobacter and Escherichia were identified to be the possible host of tet (X) and ESBL gene bla CTX-M in aquaculture, respectively. To the best of our knowledge, this is the first metagenomic study to analyze differences in resistome profiles between integrated and monoculture ponds. Overall, integrated aquaculture systems exhibited a higher prevalence of resistance genes compared with monoculture freshwater aquaculture farms. Therefore, additional antimicrobial resistance surveillance should be focused on this type of freshwater aquaculture system.